Dermal melanocytosis - V. D. Ljah; V. V. Gagiev; M. A. Ufimtseva; I. P. Nikulin; I. N. Vorozhejkina; A. S. Shubina; N. V. Simonova (Лечащий Врач, 2021)
The article describes the clinical cases of patients with nevus Ota, Mongolian spot. Many of dermal melanosis can be associated with a risk of damage to the organs of hearing, vision, nervous system and melanoma development. Therefore, such patients need dispensary observation and examination by narrow specialists. Methods of laser therapy for dermal melanocytosis are described.